Development of Teaching Module for the Merdeka Curriculum with Nuances Critical Reasoning for Elementary School Students - Angelina, Angelina; Bistari, Bistari; Halidjah, Siti (Universitas Pendidikan Mandalika, 2024)
This research aims to develop a teaching module for the Merdeka Curriculum with nuances of critical reasoning for elementary school students. It does this by outlining the validity level assessed from the teaching module's suitability aspect, language aspects, and empirical validity of the practicality level of the module. This study used the research and development method with the 4D model, which involved definition, design, development, and dissemination. The instruments used in this research included validation sheets, interviews, teacher and student questionnaires, field trials, and trial observation checklists. Data analysis techniques involved qualitative content analysis and descriptive statistics. The findings demonstrated that three of the four stages, define, design, and development, were completed to construct the teaching module. The curriculum analysis, teaching module needs analysis, learning outcomes analysis, and material analysis are completed during the define step. Designing instructional modules that satisfy requirements for viability, correctness, clarity, and attractive presentation is the design stage process. Teaching module products were put through testing, validation procedures, and practicality checks to complete the development stage. The average percentage of the language component and the appropriateness aspect in the validity of the teaching module were 4.87 and 4.81, respectively, with very valid criteria. Based on teacher answer questionnaires (4.6 with very practical criteria) and student response questionnaires (4.2 with very practical criteria), the practicality of the teaching module was determined. Based on these results, the teaching module is valid and practical, so it qualifies as a feasible and quality development product.